ARTIFICIAL INTELLIGENCE SEBUAH INOVASI ATAU KEMUNAFIKAN INTELEKTUAL: KAJIAN FILSAFAT TEKNOLOGI DALAM PEMIKIRAN NICK BOSTROM - Ester Yosia; Yohanes Emanuel (CREDENDUM: Jurnal Pendidikan Agama, 2026)
The primary focus of this paper is to examine the impact of AI development on human cognitive abilities. Humans are rational beings with the ability to continually adapt both intellectually and creatively to meet the needs and advancements of the times. However, in recent decades, human cognitive abilities have been declining, particularly among children in school, with many exhibiting symptoms of “brain rot.” “brain decay” a phenomenon influenced by the unwise and inappropriate use of AI. This is because AI systems operate by providing convenience to the human brain through various advanced artificial intelligence features; thus, if used indiscriminately without limits, the human brain ceases to be productive and is no longer utilized to its fullest potential for thinking or conceptualizing. It is this concern that subsequently prompted the author to examine this issue, whether Artificial Intelligence is an intellectual innovation or merely intellectual hypocrisy. Nick Bostrom, a philosopher of technology, views AI through the lens of human-defined objectives. Additionally, Nick Bostrom examines AI ontologically, given that AI’s functional capabilities surpass those of humans, necessitating that humans use AI wisely. Ultimately, this research will broaden the perspective that, ontologically, AI is a tool to assist humans in developing life, not a tool to deceive the public in research.